Charring-induced morphological changes of Chinese “Five Grains”: An experimental study - Liu, Yang; Xi, Yang; Zhang, Fei; Wang, Zhenzhen; Wang, Can; Yu, Shiyong; Chen, Xuexiang (Frontiers in Plant Science, 2023)
Charring process affects the preservation potential of seeds, resulting in limited perceptions of crop assemblages recovered from archaeological layers. Therefore, the specifics of the charring process deserve further investigation. Colloquially referred to as the “Five Grains” (五谷), bread wheat (Triticum aestivum), foxtail millet (Setaria italica), broomcorn millet (Panicum miliaceum), rice (Oryza sativa), and soybean (Glycine max) represent a set of four major cultivated cereals and a pulse constituting crucial staple food in Chinese history and the most frequently discovered crops at archaeological sites in China. This paper aims to understand the changes in size, volume, and weight loss of grains under variable aerobic charring conditions. The size and weight were measured for the untreated specimens and the specimens heated at different temperatures and over different time-periods. We found that temperature and exposure time directly affected the grain size. Specifically, the grains of most species shrank at lower temperatures and expanded rapidly at higher temperatures. Among the “Five Grains”, soybean was the type least affected by charring, followed by wheat, rice, and millet. Volume and weight can be used as conversion factors to minimize the bias in quantitative representation due to varied charring preservation potential. For rice, wheat and soybean, the variation in volume is smaller. For millet, both volume and weight can be used as the control to understand the consequences of charring for the assemblage. Further experiments and comparisons of ancient samples are needed in future studies to investigate other factors that affect the preservation of charred plant remains.